Analisis Pendapatan dan Pemasaran Pekebak Ikan (Pelet Keong Bakau Pakan Ikan) di Kota Langsa - Rini Mastuti; Sorbakti Sinaga; Agustinus Sinaga; Derri Irawan; Mustika Purba (SULUH: Jurnal Abdimas, 2020)
Pellets are a source of energy intake made by humans with certain compositions needed according to an aquatic organism. The need for artificial feed (pellets) will greatly support the success of cultivation. A good pellet will produce fast fish growth so the production costs are not too high. Feed on a fish is not the same because it must be adapted to the type of commodity and its eating habits. Good food is a food that has high protein and is easily obtained. One of them is mangrove snails (T. telescopium). Kuala Langsa is a village located in the city of Langsa which is directly adjacent to the Malacca Strait so that in this area mangroves are found. The advantage of this pellet is that it is easy to find mangrove snail base material and its availability is abundant so that later the price will be cheaper with higher quality protein content compared to the pellets available on the market. The benefits of making this pellet are: (1). The creation of quality fish feed pellets, as an alternative to fish feed. (2). As an application of the science of fish feed from college, and (3). As an application of entrepreneurship science, to hone skills and soft skills entrepreneurs, so that they are ready to become independent entrepreneurs when they graduate. This pellet has a value of R / C ratio of 1.33, which means that every capital issued in the amount of Rp. 100.00 will get an income of Rp. 137.00. Thus, the fish pellet feed business is feasible to be developed.